The Campbell Bonner Magical Gems Database - Dzwiza, Kirsten (Museum of Fine Arts, 2010)
[Dt.:] Das Ziel der Campbell Bonner Magical Gems Database (CBD), benannt nach dem gleichnamigen Altertumswissenschaftler, ist es, einen Korpus der gesamten magischen Gemmen online zu stellen. Die Datenbank, die seit 2010 im Internet steht, ist nach verschiedensten Kriterien durchsuchbar und bietet u.a. ein Glossar sowie eine thematische Bibliographie. - [Engl.:] Named after Bonner, the primary aim of the Campbell Bonner Magical Gems Database (CBd) is to bring the entire corpus of magical gems online in order to make them better accessible for both scholars and the public, and to facilitate their study through the potentials offered by a digital database. Since its launch in 2010 the database has grown to be a much used research tool, and has helped recognize the genre of magical gems as an important object group of the classical material tradition.
Gesehen am 28.04.15
Keywords: Datenbank; Magie; Gemme; Römisches Reich